Institutionalization of the Department of Global and National-Ecological Policies and Possibility of Functional Hormony (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article discusses the organization and support of the regional ecological balance, which is the most urgent problem of our time, its development on the basis of modern technologies, management orientation based on the latest concepts and further improvement of the system.